The element occupation preference of μ phase in ternary Ni-Cr-Mo model superalloy - Peng Dong; Xuesong Pei; Xiaona Zhang; Lin Ge; Naidan Hu; Hui Li; Ze Zhang (Materials & Design, 2023)
Topologically close-packed (TCP) phases seriously endanger the properties of Superalloy. Investigating the microstructure of the TCP phases will provide a crystallographic reference for the design of superalloys with better properties. The μ phase is a common TCP phase in superalloys. It belongs to the space group R-3m, and has a hexagonal structure with five Wyckoff sites of 3a, 18h, 6c1, 6c2 and 6c3. In this paper, occupation of the three kinds of atoms at five Wyckoff sites of the μ phase in Ni-Cr-Mo model superalloy was determined using aberration-corrected High-Angle Annular Dark-Field Scanning Transmission Electron Microscopy (HAADF-STEM), QSTEM software simulation and first-principles calculations. It was found that Mo atoms with larger size and smaller electronegativity tend to occupy 6c3, 6c1 and 6c2 sites in order of priority. Ni atoms mainly occupy the sites with coordination number (CN) of 12 at 3a and 18 h, and 3a sites contain more Cr atoms than 18 h sites.